EFFECT OF NITROGEN AND PHOSPHORUS FERTILIZERS ON GROWTH AND YIELD OF SOME LEGUMINOUS FORAGES - Mohamed, G.G.; Abusuwar, A.A. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text